Determination of Tenacissoside G, Tenacissoside H, and Tenacissoside I in Rat Plasma by UPLC-MS/MS and Their Pharmacokinetics - Fan Chen; Yizhe Ma; Ying Cui; Wanhang Wang; Chenchen Mei; Jingjing Nie; Congcong Wen; Xiuwei Shen; Xuzhao Zhou (International Journal of Analytical Chemistry)
An ultra-performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) method was developed for the determination of tenacissoside G, tenacissoside H, and tenacissoside I in rat plasma. The rat plasma was treated with liquid-liquid extraction using ethyl acetate. The determination was performed on the UPLC HSS T3 column (50 mm × 2.1 mm, 1.8 μm) with a mobile phase consisting of acetonitrile-water (containing 0.1% formic acid) and gradient elution at a flow rate of 0.4 mL/min. Electrospray (ESI) positive ion mode detection and multireaction monitoring (MRM) quantitative analysis were performed. A total of 36 rats were given tenacissoside G, tenacissoside H, and tenacissoside I, respectively, orally (5 mg/kg) and intravenously (1 mg/kg), with 6 rats in each group, to evaluate the pharmacokinetic difference of tenacissoside G, tenacissoside H, and tenacissoside I in rats. The calibration curves showed good linearity in the range of 5–2000 ng/mL, where r was greater than 0.99. The results of precision, accuracy, recovery, matrix effect, and stability met the requirements of biological sample detection methods. The established UPLC-MS/MS method was successfully applied to pharmacokinetic studies of tenacissoside G, tenacissoside H, and tenacissoside I, and the bioavailability was 22.9%, 89.8%, and 9.4%, respectively.